Influence of Oxidized Low Density Lipoprotein on the Proliferation of Human Artery Smooth Muscle Cells in vitro - 乔晨晖 张凯伦 夏家红 (Journal of Huazhong University of Science and Technology. Medical sciences, 2007)
The effects of oxidized low density lipoprotein （ox-LDL） on the proliferation of cultured human vascular smooth muscle cells （vSMC） were investigated in vitro. By using NaBr density gradient centrifugation, LDL was isolated and purified from human plasma. Ox-LDL was produced from LDL by being incubated with CuSO4. ox-LDL was then added to the culture medium at different concentrations （35, 60, 85, 110, 135 and 160μg/mL） for 7 days. The influence of ox-LDL on vSMC proliferation was observed in growth curve, mitosis index, and in situ determination of apoptosis. The data were analyzed with SPSS 10.0 software. The results showed that the ox-LDL produced in vitro had a good purity and optimal oxidative degree, which was similar to the intrinsic ox-LDL in atherosclerotic plaque, ox-LDL at a concentration of 35 μg/mL demonstrated the strongest proliferation inducement, and at a concentration of 135 μg/mL, ox-LDL could inhibit the growth of vSMC. ox-LDL at concentrations of 35 and 50 μg/mL presented powerful mitotic trigger, and with the increase of ox-LDL concentration, the mitotic index of vSMC was decreased gradually, ox-LDL at higher concentrations promoted more apoptotic vSMCs, ox-LDL at lower concentrations triggered proliferation of vSMCs, and at higher concentrations induced apoptosis in vSMCs, ox-LDL played a promotional role in the pathogenesis and development of atherosclerosis by affecting vSMC proliferation and apoptosis.